Experiences, perspectives, and practice patterns of pulmonary embolism follow-up in Denmark. A mixed method study informing the development of A sTrucTurEd INtegrateD post PE care model. (3rd October 2022) - Hoejen, A A; Larsen, T B; Hansen, A S; Johnsen, S P; Rolving, N
Abstract: Background: Practice patterns of follow-up after pulmonary embolism (PE) varies both within and between countries, and high-quality evidence to provide clinical guidance is lacking [1, 2]. This study is part of the trial – A sTrucTurEd INtegrateD post Pulmonary Embolism care model (Attend-PE) aimed at developing and testing the effectiveness of a structured, integrated and patient-centered follow-up care model for patients with PE. Purpose: To explore experiences, perspectives, and practice patterns of PE follow-up. Ultimately identifying and describing the opportunity space for a structured integrated post PE care model. Methods: We performed a convergent mixed method study based on data from patient journey mapping including surveys, observations, and semi-structured patient interviews across all main hospitals treating PE in Denmark. An integrated mixed methods interpretation was conducted using joint displays. Results: Main results are presented in joint displays in Figure 1 and 2. Observations and surveys were conducted at 18 hospitals including 12 in-depth patient-interviews. The structure of care varied greatly. Patients expressed a need for early follow up and specialist care but at 18% of the sites first follow-up visit was not until 3–6 months after PE and 24% of the sites only had in-person contact with patients when follow-up echocardiography was needed. At some sites it was also highlighted that not all patients were referred to the post PE follow-up. anticoagulation clinics. Further, transition of care to the general practitioner was identified as a particular challenge. All sites considered Non-vitamin K antagonist oral anticoagulants the preferred anticoagulant treatment with low-molecular-weight heparins/Vitamin K antagonists as second choice. The possible need for extended treatment and reduced dose favored Rivaroxaban and Apixaban. The decision on treatment duration was most often taken at the 3–6-month follow-up visit, and patients described the decision on extended treatment as positive and reassuring. Patient information (oral and written) varied greatly and was most often focused on anticoagulant treatment, while knowledge on PE in general, symptom management, and activity was scarce. Two sites offered structured group-based patient education, but unstructured patient education at the individual follow-up visits was most common. Help and guidance on managing post-PE symptoms and returning to everyday life was perceived essential by patients, as it affected them both physically and mentally. However, none of the sites routinely offered or referred patients to rehabilitation. Involvement of relatives was considered important but 33% of the hospital sites did not systematically encourage relatives to attend follow-up. Conclusion: The considerable variation in structure of PE follow-up care demonstrated in this mixed method study highlights the need for a structured integrated post pulmonary embolism care model. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The Danish Heart AssociationThe Novo Nordisk Foundation